The effect of desloratadine on ischemia reperfusion induced oxidative and inflammatory renal injury in rats - Huseyin Kocaturk; Fevzi Bedir; Mehmet Sefa Altay; Ebubekir Bakan; Bahadir Suleyman; Gulce Naz Yazici; Mukadder Sunar; Zeynep Suleyman; Halis Suleyman (Renal Failure, 2020)
Purpose To examine the effect of desloratadine on kidney ischemia-reperfusion (I/R) injury in albino Wistar male rats using biochemical and histopathological methods. Methods The treated with ischemia–reperfusion + 5 mg/kg desloratadine (IRD) group (n–6) was given 5 mg/kg desloratadine by gavage orally, and applied renal ischemia-reperfusion (BIR) group (n–6) and control (SG) group undergoing Sham operation (n–6) rats were given distilled water as solvent one hour before ketamine anesthesia. During the anesthesia period, ischemia was induced for 2 h unilaterally in the left kidney of all rats followed by reperfusion for 6 h. The kidneys of the SG group had sham operation without any intervention. Results Our biochemical test results showed that malondialdehyde (MDA), nuclear factor kappa (NF-κB), tumor necrosis factor alpha (TNF-α), interleukin one beta (IL-1β), creatinine, and blood urea nitrogen (BUN) levels were significantly increased in the BIR group compared to the healthy control and IRD groups treated with desloratadine. Histopathological results were revealed tubular dilatation, tubular necrosis, loss of brushy margins, cast formation, and apoptotic bodies in tubular epithelial cells in the BIR group. There were no histopathological findings except for the swelling of tubule epithelial cells and the accumulation of proteinous material in some tubule lumens in renal tissue of desloratadine-treated rats. Conclusions Experimental results suggested that desloratadine may be useful in the treatment of renal I/R injury.